Le M'Zab : La conquête. Le pays et ses ressources. Son rôle dans la colonisation - Masson, Paul (Bulletin de la Société de géographie de Saint-Quentin, 1889)
Keywords: Moeurs et coutumes -- Mzab

Art. IX.—The O'mánee Dialect of Arabic - Jayakar, A. S. G. (The Journal of the Royal Asiatic Society of Great Britain and Ireland, 1889)
Keywords: Linguistique -- Oman

Art. XI.—The O'mánee Dialect of Arabic - Jayakar, A. S. G. (Journal of the Royal Asiatic Society, 1889)
In compiling the following vocabulary of 'Omanee words, the principal aim has been to give only such words as exhibit the dialectical peculiarities mentioned in the preceding Part, and not to furnish a complete list of words in common use in O'mán. Technical words, or words employed in agriculture, trade, arts, manufactures, etc., have been intentionally omitted, as they would be beyond the scope and extent of the present paper. Most of the words, it will be seen, are of Arabic origin, and the dialectical sense, wherever it differs from the original, is either metaphorical or an extension of the sense conveyed by the original root.
Keywords: Linguistique -- Oman

General Ben Ayad’s property - Read, T. (Further Correspondance respecting the Affairs of Tunis, 1889)
Keywords: Famille Bin Ayyad

General Ben Ayad’s claim - Read, T. (Further Correspondance respecting the Affairs of Tunis, 1889)
Keywords: Famille Bin Ayyad

Bericht des Dr. Ulrich Zasius über die Einnahme von Dscherba durch die Türken 1560 - Wachter, F. (Zeitschrift des Bergischen Geschichtsvereins, 1889)
Keywords: Invasions chrétiennes -- Djerba -- 1560